Power of plant microbiome: A sustainable approach for agricultural resilience - Qurban Ali; Mohsin Ali; Huang Jing; Amjad Hussain; Hakim Manghwar; Musrat Ali; Waseem Raza; Sunil Mundra (Plant Stress)
Plants encounter various biotic and abiotic stresses throughout their lifecycle, which can adversely impact their productivity and lead to yield loss. This ultimately results in a significant decline in food production with global pressure on declining agriculture. The agrochemical pesticides have been proven effective in controlling various diseases in major crops, their excessive use poses significant risks to the environment and human health and negatively impacts non-target host microbiota. Novel approaches in the form of host plant microbiome as an alternative strategy to overcome these stresses have recently gained increasing attention. Emerging evidence suggests that plants subjected to biotic and abiotic stress experience diverse microbial local (diffusible) and distant (volatile organic compounds) metabolites and respond with the expression of defense genes (transcriptomic variations) that result in changing leaf and root exudates and alter resident microbial community structure. The relative abundance of symbiotic microorganisms under stress may favor plant survival and enhance adaptation during stress. Thus, to counter the negative effects, introducing an efficient microbiome into the host crop is highly desirable due to the attractive functional potential of the phytomicrobiome. Here, we summarize more effective and reproducible strategies to use microbial activities in crop production and protection to promote a suitable agricultural environment. In addition, detailed molecular mechanisms of phytomicrobiome in stimulating plant immune system, the interaction between microbiome and plant defense system, and defense strategies of microbiome against biotic and abiotic factors have been described. Finally, we explored the plant-based strategies for microbiome engineering and bioinformatics methods to predict microbiome functions.